Pengaruh Pembiayaan Murabahah, Pembiayaan Musyarakah Dan Pembiayaan Mudharabah Terhadap Profitabilitas Bank Syariah (Studi Kasus pada PT. Bank Muamalat Indonesia, Tbk.) - Hasanah, Akfina, Drs. H. Agus Endro Suwarno, M.Si (2015)
Islamic banking services related to services offered by a bank syariah financing terkemas in the products which is in a sharia bank , one of which is typical of syariah bank is purchasing or selling by means of financing called murabahah and financing for the results of which is based and musyarakah mudharabah .This research aims to analyse the influence of financing murabahahah , on the level of profitability and mudharabah musyarakah in bank muamalat indonesia by using the ratio of return on assets ( roa ). The research method used is descriptive quantitative approach of research and case studies on PT Bank Muamalat Indonesia, Tbk. Types of data obtained from this research is secondary data based on quarterly financial reports from the results of Bank Muamalat Indonesia during the 2004 annual period up to 2011. Data sources obtained through publication results by PT Bank Muamalat Indonesia. Analysis tools are used multiple linear regression analysis. The research results show that the financing murabahah and musyarakah to exert an influence on the level of negative and significant roa , while financing mudharabah give a positive influence on the level of roa and significant partial evaluation .Simultaneously , murabahah financing , mudharabah and musyarakah this provides significant influence on the level of roa .Mudharabah financing is financing for the best influences the level of roa dominant .